In Working Order: Health and Wellbeing among Workers in the Republic of Ireland and Northern Ireland - Belizón Cebada, María Jesús; Hassard, Juliet; Geary, John (My University, 2026)
Este informe presenta los resultados de la Working in Ireland Survey 2025 sobre salud, bienestar y condiciones psicosociales de trabajo en la República de Irlanda e Irlanda del Norte. El estudio analiza el estado general de salud de los trabajadores, el bienestar psicológico, el estrés laboral y síntomas tempranos de riesgo como fatiga, baja energía y tensión emocional. También examina diferencias por sector, tipo de contrato, jornada, edad, género, nivel educativo, afiliación sindical y otros factores laborales. Los resultados muestran una situación general positiva, aunque con grupos y sectores más expuestos a peores resultados de salud y bienestar. El informe subraya la importancia de prevenir riesgos psicosociales, mejorar la calidad del empleo, reforzar el apoyo directivo y promover políticas laborales centradas en el bienestar.

This report presents findings from the 2025 Working in Ireland Survey on worker health, wellbeing, and psychosocial working conditions in the Republic of Ireland and Northern Ireland. It examines general health, psychological wellbeing, work-related stress, and early indicators of risk such as fatigue, low energy, and emotional strain. The report also explores differences across sectors, contract types, working time patterns, age, gender, education level, trade union membership, and other workplace factors. Overall, workers report a generally positive health profile, but specific groups and sectors show higher exposure to poorer health and wellbeing outcomes. The findings highlight the importance of preventing psychosocial risks, improving job quality, strengthening supportive management practices, and embedding wellbeing within employment policy and organisational practice.
Informe técnico